Thermodynamic and spectroscopic properties of oxygen on silver under an oxygen atmosphere. Issue 14 (11th March 2015) - Jones, Travis E.; Rocha, Tulio C. R.; Knop-Gericke, Axel; Stampfl, Catherine; Schlögl, Robert; Piccinin, Simone
Abstract : Comparing experimental and theoretical XPS and XANES suggest that unreconstructed atomic oxygen is not present on the silver surface at oxygen chemical potentials relevant for epoxidation. Abstract : We report on a combined density functional theory and the experimental study of the O1s binding energies and X-ray Absorption Near Edge Structure (XANES) of a variety of oxygen species on Ag(111) and Ag(110) surfaces. Our theoretical spectra agree with our measured results for known structures, including the p ( N × 1) reconstruction of the Ag(110) surface and the p (4 × 4) reconstruction of the Ag(111) surface. Combining the O1s binding energy and XANES spectra yields unique spectroscopic fingerprints, allowing us to show that unreconstructed atomic oxygen is likely not present on either surface under equilibrium conditions at oxygen chemical potentials typical for ethylene epoxidation. Furthermore, we find no adsorbed or dissolved atomic species whose calculated spectroscopic features agree with those measured for the oxygen species believed to catalyze the partial oxidation of ethylene.